Engineering (Hilah) Of Guardians For Child Marriage Of Admiral From an Islamic Law Perspective - Muhsin Luki; Syamsu Madyan; Dzulfikar Rodafi (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
The adulterous child marriage that occurred in Sreseh District, Sampang presents a dilemma between normative rules that require a guardian judge and the practice of engineering marriage guardians for social interests, so this empirical legal research through literature study, interviews, observations, and documentation examines the hilah pattern, motivation, impact, and Islamic legal review. Thus, four patterns were identified: taukil biological father to guardian judge, contract in a closed place that was then announced, double contract by biological father and guardian judge, and unregistered marriage with taqlid Hanafi school or walimuhakkam. Engineering is driven by the desire to cover up shame, maintain social conduciveness, prevent the annulment of the marriage by the groom, and guarantee the validity of the contract, but has an impact on reducing household harmony to divorce. From the fiqh perspective, a marriage remains valid because the contract is ratified by a judge or by the school of thought followed, while the validity of manipulation depends on the harm: it is permitted if it prevents disturbances or anarchy, but is forbidden if it is solely for the benefit of the bride's family so that the marriage is not considered.